Policy formulation of storm water detention schemes and its effectiveness in urban residential zones - Ancheta, Maria Anjelica P.
Due to the rapid increase of urbanization and growth of residential areas in the Philippines, most especially in Metro Manila, the volume of surface runoff in these areas increases. Furthermore, urbanization has also brought along governance problems that led to uncontrollable behaviour, such as improper waste management, uncoordinated development plans and all others. Thus, drainage easements become clogged and when there is heavy rainfall, flooding easily occurs. In order to counteract these problems, the study formulated a governing policy that combined both the institutional and technical aspects that will make use of detention basins as storm water mitigation schemes in residential zones in possibly all over the country. The technical aspect of the policy was developed through modelling a current and new drainage scheme of a familiar subdivision of the New Intramuros Village in District 3 in Quezon City using Storm Water Management Model (SWMM), while the institutional policy shall be based on in-depth analysis in lieu with urban planning.